Protective effects of vitamin C and vitamin E against hysterosalpingography-induced epithelial degeneration and proliferation in rat endometrium - Pala, Sehmus; Atilgan, Remzi; Kuloglu, Tuncay; Kara, Murat; Baspinar, Melike; Can, Behzat; Artas, Gokhan (Dove Medical Press Ltd, 2016)
Aim: The aim of this study was to examine the protective effects of vitamin C (VC) and vitamin E (VE) against hysterosalpingography (HSG)-induced epithelial degeneration and proliferation in rat endometrium. Materials and methods: A total of 28 female Wistar albino rats were randomized into four groups: G1 (n=7; abdomen was opened and closed), G2 (n=7; 0.1 mL Lipiodol [ ethiodized oil] was administered to each uterine horn in conjunction with X-ray irradiation), G3 (n=7; 50 mg/kg of intraperitoneal (ip) VC was administered, followed by the administration of 0.1 mL of ethiodized oil into the uterine horns after 15 minutes), and G4 (n=7; 50 mg/kg of ip VE was administered, followed by the administration of 0.1 mL of ethiodized oil into the uterine horns after 15 minutes). After abdominal closure, rats in G2, G3 and G4 groups were exposed to whole-body X-irradiation three times with 2-minute intervals at a total dose of 15-20 mrad. Three hours after exposure, abdominal cavities of all the rats were reopened and uterine horns were removed. The right uterine horns were embedded into paraffin blocks after fixing in 10% formaldehyde for histopathological and immunohistochemical examination. Uterine horns on the other side were rapidly excised and stored at -80 degrees C for the examination of expression of microRNAs (miRNAs) and oxidant, antioxidant, apoptotic and antiapoptotic gene expression using real-time polymerase chain reaction (RT-PCR) method. Results: No differences were observed in terms of expression of miRNAs and oxidant, antioxidant, apoptotic and anti-apoptotic gene expression between the study groups. Congestion, epithelial degeneration and malondialdehyde immunoreactivity were significantly lower in G3 and G4 groups than in G2 group; no differences were observed between G1, G3 and G4 groups. Ki-67 immunoreactivity score was significantly higher in G2 group when compared with G1, G3 and G4 groups. Caspase-3 immunoreactivity was not statistically different between the groups. Conclusion: VC and VE may confer cellular protection against radiation injury induced by HSG in endometrial epithelium.
Keywords: vitamin C; vitamin E; radiation; endometrium; rat; miRNA